A facile self-template strategy for synthesizing 1D porous Ni@C nanorods towards efficient microwave absorption. (16th February 2017) - Zhang, Yanan; Zhang, Xingmiao; Quan, Bin; Ji, Guangbin; Liang, Xiaohui; Liu, Wei; Du, Youwei
Abstract: Ni@C composites, which simultaneously possess porous, core–shell and 1D nanostructures have been synthesized with a facile self-template strategy. The precursors were obtained by a hydrothermal process using NiCl2 · 6H2 O and nitrilotriacetic acid as the starting material and then annealed at 400 °C, 500 °C, and 600 °C. The Ni@C composites annealed at 500 °C display a nanorod feature with a length of ∼3 μ m and diameter of 230–500 nm. In addition, about 3 nm carbon shells and 4 nm Ni cores can be found in Ni@C nanorods. Attributed to the interconnected mesoporous texture in nanorods, strengthened interfacial polarization from core–shell structure, and better impedance matching benefiting from a great deal of pores, Ni@C nanorod composites exhibit perfect microwave absorption performance. The minimum reflection loss (RL) value of −26.3 dB can be gained at 10.8 GHz with a thickness of 2.3 mm. Moreover, the effective bandwidth (RL ≤ −10 dB) can be achieved, 5.2 GHz (12.24–17.4 GHz) under an absorber thickness of 1.8 mm, indicating its great potential in the microwave absorption field. Considering this technique is facile and effective, our study may provide a good reference for the synthesis of 1D carbon-based microwave absorbers with core–shell nanostructure.